The Influence of Forming Effects on The Bending Crush Behavior of Top-Hat ThinâWalled Beams - Santosa, Sigit Puji; Nhat Vu, Nguyen Van; Gunawan, Leonardo; Jusuf, Annisa (Mesin, 2016)
This paper presents a study on the effects of forming process of a topâhat thinâwalled beams to its bending crush resistance under dynamic bending load. The thinâwalled beam was formed using a one step deep drawing. HyperForm software simulated the forming process and mapped its effects such as thickness variations and residual plastic strains in to the crash analysis models. Then the dynamic bending crush analysis was carried out using LSâDYNA by using the geometry and materials data obtained from the forming analysis results. For each material model, the analyses were carried out for model with and without the forming effects. The bending crush behavior of the topâhat thinâwalled beams were then analyzed to compare between the simulations with and without forming effects. The results show that by incorporating the effect of forming process, the bending crush resistance of the thinâwalledÂ beams is increase by 4.7%. The introduction of strain rates to the material model increases even further on the bending crush resistance of the thinâwalledÂ beam.